IMPLEMENTASI RISK-BASED INTERNAL AUDIT SEBAGAI TEROBOSAN ANTI-FRAUD PROCUREMENT DALAM INDUSTRI REAL ESTATE : (Studi pada PT. XYZ) - Rahardiansyah, Risal Fadhil (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2024)
Abstract: This research aims to propose an anti-fraud breakthrough in the real estate industry, focusing on the procurement process at PT XYZ. This research identifies fraud risks through the risk-based internal audit approach, such as direct appointment without a tender process and lack of control in collecting price quotations. A solution was proposed in the form of an e-procurement system model that includes dual control, historical data-based contractor evaluation, contractor financial analysis, and the application of a bank guarantee clause. The research method uses a qualitative approach with case studies, collecting primary data through observation and interviews and secondary data through literature studies. By involving Risk-Based Internal Audit (RBIA), the research designed concrete measures to improve transparency and security in every stage of the procurement process. The proposed e-procurement system is designed as a web-based platform connected to contractors via the internet, providing the potential for increased efficiency of administrative processes. Abstrak: Penelitian ini bertujuan mengusulkan terobosan anti-fraud dalam industri real estate, fokus pada proses procurement di PT XYZ. Melalui pendekatan Risk Based Internal Audit, penelitian ini mengidentifikasi risiko kecurangan, seperti penunjukkan langsung tanpa proses tender dan kurangnya kontrol dalam pengumpulan penawaran harga. Solusi diusulkan berupa model sistem e-procurement yang mencakup dual kontrol, evaluasi kontraktor berbasis data historis, analisis keuangan kontraktor, dan penerapan klausul Bank Guarantee. Metode penelitian menggunakan pendekatan kualitatif dengan studi kasus, mengumpulkan data primer melalui observasi dan wawancara serta data sekunder melalui studi literatur. Dengan melibatkan Internal Audit Berbasis Risiko (RBIA), penelitian ini merancang langkah-langkah konkret untuk meningkatkan transparansi dan keamanan dalam setiap tahap proses pengadaan. Sistem e-procurement yang diusulkan dirancang sebagai platform berbasis web terkoneksi dengan kontraktor melalui internet, memberikan potensi peningkatan efisiensi proses administratif.